2022
DOI: 10.3390/membranes12060584
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solution Casting Temperature and Ultrasound Treatment on PEBAX MH-1657/ZIF-8 Mixed Matrix Membranes Morphology and Performance

Abstract: Approximately two-thirds of anthropogenic emissions causing global warming are from carbon dioxide. Carbon capture is essential, with membranes proving to be a low cost and energy-efficient solution to alternative technologies. In particular, mixed matrix membranes (MMMs) can have higher permeability and selectivity than pure polymer membranes. The fabrication conditions affect the formation of defects within the membranes. In this work, MMMs were created using a PEBAX MH-1657 polymer and a ZIF-8 filler. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…These results were compared to other PEBAX-ZIF hybrid membranes reported in the literature (Table ). ,, The membranes with ZIF-7/COK-17 45 (S) achieved a significant enhancement in CO 2 /N 2 selectivity with no detriment to the permeability, while other studies reported an increase in permeability but no gains for the selectivity. This difference can partially be attributed to the preparation of the membrane (PEBAX and MMM).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…These results were compared to other PEBAX-ZIF hybrid membranes reported in the literature (Table ). ,, The membranes with ZIF-7/COK-17 45 (S) achieved a significant enhancement in CO 2 /N 2 selectivity with no detriment to the permeability, while other studies reported an increase in permeability but no gains for the selectivity. This difference can partially be attributed to the preparation of the membrane (PEBAX and MMM).…”
Section: Resultsmentioning
confidence: 87%
“…This difference can partially be attributed to the preparation of the membrane (PEBAX and MMM). The fabrication conditions (i.e., temperature, ultrasound treatment) have an impact on the separation performances of PEBAX, 51 which explains the difference in the performance of the pure polymer in the literature. As a consequence, the addition of selective fillers can have a lower relative impact in some cases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%